Avaliação comportamental e neurobiológica da memória no lagarto Tropidurus hispidus (SPIX, 1825 ; Squamata : Tropiduridae) - Santos, Luciano de Gois (2016)
In the group of reptiles, the ability to form memories is still much discussed and neuroanatomical data have suggested the existence of homologies between the areas of the hippocampus and amygdala of mammals and correlated structures of the telencephalon of reptiles. However, there is little functional evidence of these structures in reptiles to give support to this proposal homology. Faced with this situation, this study aimed to conduct a behavioral and neurobiological evaluation of memory in lizards species Tropidurus hispidus. For this, were used 50 lizards adult males, which after 4 days of accommodation were distributed in two experiments: the Experiment 1, aversive memory (n = 40); and the Experiment 2, spatial memory (n = 10). In Experiment 1, the animals were divided into three groups (Control, n = 8; Neutral Stimulus, n = 16; Aversive Stimulus, n = 16). The Control group did not participate in the behavioral steps, since the Neutral Stimulus group was exposed to an empty metal cage, while the Aversive Stimulus group was exposed to a domestic cat. Then all the animals in the Control group and half of the animals Neutral Stimulus and Stimulus Aversive groups had their brains perfused with paraformaldehyde 4% for subsequent analysis. The remaining animals of Neutral and Aversive Stimulus groups returned to the accommodation terrarium and, after 24 hours, passed by a rechallenge to local display of the stimulus, then also had their brains perfused with paraformaldehyde 4%. After fixation, brains were all collected subjected to a imustotoquímica detection technique the ZIF-268, a protein involved in mediating plasticity which occurs during memory formation. We found that during exposure to cat lizards of Aversive Stimulus group had a higher freezing time (p <0.001) and a smaller number of initiated movements (p <0.001) and visited quadrants (p <0.001) when compared with Neutral Stimulus group. Also found that during the re-exposure to aversive environment, the animals Aversive Stimulus group had a higher freezing time (p <0.001) and a smaller number of initiated movements (p <0.001) and visited quadrants (p <0.001), suggesting so that exposure to cat served adequately as an aversive stimulus. There was also an increase in the number of Zif-268 positive cells in regions of the reptilian hippocampus and amygdala lizards Stimulus Aversive group during exposure to cat (p = 0.005 and p = 0.039, respectively) and on re-exposure to aversive context (p = 0.001 and p = 0.009, respectively). In experiment 2, lizards underwent an adaptation of the Morris water maze, where 3 times a day for 19 days, the animals had performed attempts to find a submerged platform. We found a negative correlation (p = 0.012) the time to reach the platform and over the days, indicating an improvement in the performance of lizards in the task. Thus, the present study provided evidence that males of T. hispidus are capable of forming aversive and spatial memories, and that there is an involvement of the hippocampus and amygdala in aversive memory.